The Hindu way :an introduction to Hinduism - Shashi Tharoor (Aleph, 2019)
The Hindu Way: An Introduction to Hinduism, the new book by bestselling author Shashi Tharoor, whose last three books have sold over a quarter of a million copies in hardback, is the perfect introduction to one of the world's oldest, largest and most complex religions. Although there are hundreds of books on Hinduism, there are only a few which provide a lucid, accessible, yet deeply layered account of the religion's numerous belief systems, schools of thought, sects, tenets, scriptures, deities, rituals, customs, festivals and philosophies. This book is one of them.